International Monetary Cooperation Since Bretton Woods - James, Harold 1956- (International Monetary Fund, 1996)
This comprehensive history, published jointly by the IMF and Oxford University Press, was written to mark the fiftieth anniversary of international monetary cooperation. From the establishment of the postwar international monetary system in 1944 to how the framework functions in a vastly expanded world economy, historian Harol James describes the tensions, negotiations, challenges, and progress of international monetary cooperation. This narrative offers a global perspective on the events and decisions that have shaped the world economy during the past fifty years
1. Interdependence in the World Economic System -- 2. "Prosperity Has No Fixed Limits" -- 3. The Compromise Unravels -- 4. Richesse Oblige: The Establishment of Convertibility -- 5. Development and Bretton Woods -- 6. The Heyday of Bretton Woods and the Reserve Debate -- 7. Surveillance, Growth, and Crisis -- 8. The End of Bretton Woods? -- 9. Reform of the International Monetary System, or Nonsystem? -- 10. Personalities and Institutions: The Redesigning of the International Monetary Order -- 11. The 1970s: Capital Markets Versus the New International Economic Order -- 12. The Debt Crisis -- 13. Consensus in Cooperation and Its Fragility -- 14. The Problems of the New Regionalism -- 15. Low-Income Countries and the International Financial System -- 16. Plan or Price? The Transformation of Centrally Planned Economies -- 17. From Bretton Woods to the Information Age
This comprehensive account of the management of the international monetary system from the 1944 Bretton Woods conference to the present day documents the structure and movements of the world economy during a period of dramatic change. Commissioned by the International Monetary Fund to mark its fiftieth anniversary, the work is nevertheless a fully independent one: written by an outside historian with full access to IMF archives and staff, and reviewed by an independent editorial committee. An objective study of issues and events that are often controversial, the book skillfully interweaves the history of the IMF with that of world economic developments after the Second World War
Keywords: Fonds monétaire international / Histoire; Geschichte 1919-1939; Geschichte 1945-1995; Política monetaria / Cooperación internacional; Instituciones financieras internacionales; Finances internationales; Politique monétaire / Coopération internationale; Institutions financières internationales; Economische samenwerking; Internationale financiële politiek; Financiële instellingen; Monetaire samenwerking; Bretton-Woods-System; Internationales Währungssystem; INTERNATIONAL FINANCE.; INTERNATIONAL MONETARY SYSTEM.; INTERNATIONAL FINANCIAL INSTITUTIONS.; BRETTON WOODS INSTITUTIONS.; Relations économiques internationales; Accords de Bretton Woods (1944); Politique monétaire; Système monétaire international / 1945-; BUSINESS & ECONOMICS / Finance; Financial institutions, International; International finance; Monetary policy / International cooperation; Wirtschaft; Monetary policy -- International cooperation; Goldpreis; Goldwährung; Weltwirtschaftskrise -- 1929-1932; USA